RANCANG BANGUN APLIKASI PENILAIAN SISWA SEKOLAH LUAR BIASA (SLB) PANCA KASIH MANOKWARI BERBASIS WEB (STUDI KASUS SLB AMBAN MANUNGGAL): STUDENT ASSESSMENT APPLICATION DESIGN WEB-BASED SCHOOL (SLB) PANCA KASIH MANOKWARI (CASE STUDY AMBAN MANUNGGAL SLB) - Thesiana kala’lembang; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2023)
Application (SLB) Design using PHP and MySQL. Laravel is a PHP framework that emphasizes simplicity and flexibility in design. Supervised by Julius P.P Naibaho and Marlinda Sangglise. The problem that exists in the Panca Kasih Special School (SLB) is how to design and build student assessment applications. At present, when teachers process student grade data, they still use the manual method in the assessment book, the grades announced are the final grades without including other value components such as assignment scores, UTS, and UAS. Therefore the compiler makes an application regarding this assessment. Based on the problems above, an Assessment Application using PHP and MySQL is needed that can be used to assist the Admin and teachers in facilitating the process of assessing student learning outcomes at the Panca Kasih Manokwari Special School (SLB). The value that is input is the value of student assignments, UTS, and UAS. Furthermore, the application displays automatically on each value that has been determined by the subject teacher. The result of making this solution is a computerized application for entering data on assessing student learning outcomes at the Panca Kasih Manokwari Special School (SLB), making it easier for teachers as instructors to input student grades into the application.